STUDY OF GOLD EXTRACTION FROM STALE TAILINGS BY AGITATION LEACHING - A. Altayeva; B. N. Surimbayev; L. S. Bolotova; Zh. Т. Bagasharova; Sh. K. Akilbekova (Academic Scientific Journal of Chemistry, 2021)
The object of research is technogenic mineral formations-tailings of the Bestube processing plant located within the Bestube gold field. Analytical and technological studies of stale tailings have been carried out. According to the results of analytical studies, the material composition of stale tails was established. The average gold content in stale tailings according to assay analyses is 0.565 g/t, silver 1.56 g/t. The tailings belong to the category of poor sulfide, oxidized raw materials. The main industrially valuable component in the tailings is gold, silver has a subordinate value, and other metals are not of industrial value. Mineralogical analysis established that stale tails are represented by quartz, muscovite, clinochlore, albite, dolomite. Studies were conducted on agitation leaching of stale tailings of the initial size (64.08% of the class –0.074 mm) and after additional grinding to the size of 90% of the class –0.074 mm. Reducing the size contributes to the dissolution of gold from the tailings: at the initial size, 66.28% of gold is dissolved, after regrinding the degree of dissolution of gold from the tailings increases to 87.23%. The results of research on agitation leaching of gold have shown a high efficiency of hydrometallurgical technology for processing stale tailings of a processing plant